How to dissolve fixed‐pie bias in negotiation? Social antecedents and the mediating effect of mental‐model adjustment. (21st May 2015) - Liu, Wu; Liu, Leigh Anne; Zhang, Jian‐Dong
Summary: Fixed‐pie bias, defined as the erroneous belief that the other negotiation party's interest is directly opposite to one's own, has been a consistent hurdle that negotiators must overcome in their efforts to achieve optimal negotiation outcomes. In this study, we explore the underlying cognitive mechanism and the social antecedents of fixed‐pie bias reduction in negotiation. Using data from a negotiation simulation with 256 participants, we found that mental‐model adjustments made by negotiators could effectively decrease fixed‐pie bias. More interestingly, we also found that negotiators were less likely to reduce fixed‐pie bias when negotiating with an in‐group member than with an out‐group member but only under a high accountability condition. Finally, we found that mental‐model adjustment mediated the effects of the aforementioned social antecedents (in‐groupness and accountability) on reduced fixed‐pie bias. We discuss the theoretical and practical implications of these findings. Copyright © 2015 John Wiley & Sons, Ltd.